The Relationship Between Socioeconomic Status and Incidence of Stunting in Toddlers at Karang Taliwang Health Center, Mataram - Jaya Putra, Rian Akka; Irawati, Deasy; Zubaidi, Fitriannisa Faradina (Universitas Ibn Khaldun Bogor, 2025)
Stunting is a condition where a child's body experiences a chronic lack of nutritional intake, especially in the first 1,000 days of life, causing the child's height not match for his age. The aim of this study was to determine the relationship between socioeconomic status and incident of stunting in toddlers at Karang Taliwang Health Center. The type of research used is observational analytics with a cross sectional approach. This study used a systematic random sampling technique to obtain a sample of 54 children consisting of stunted and non-stunted toddlers. This study uses tools and materials, namely a microtoise device, weight scale, primary data and questionnaires. The results of the study showed that the respondents who experienced the most stunting were from mothers aged 20-40 years who have toddlers aged 24-60 months who were female. In addition, stunting occurs more often from parent with middle-level education. At the employment level, fathers who work as entrepreneurs experience more stunting in their toddler, for mothers, occurs more often in mothers who do not work. The incidence of stunting occurs more often in household incomes that are less than the Mataram UMK. In conclusion, there is no significant relationship between father's education, mother's education, father's occupation, mother's occupation and household income with the incidence of stunting in toddlers at the Karang Taliwang Health Center, Mataram.